Addressing Socioeconomic Disparities for Sustainable Development - Alzena, Qirania Putri (Generasi Sains Indonesia, 2024)
This paper examines the existence of socioeconomic inequalities and their consequences and effects on sustainable development by conducting a quantitative study based on the following indicators: income inequality disparity, educational access, health access against gender disparity. The secondary sources of data were national surveys, as well as socioeconomic databases, and the descriptive statistics were used as the method to measure the levels and variations of these disparities in the population under study. The results show moderate income inequality, low levels of average education, comparatively unequal access to health care accessibility, and a continued gender gap in the rate of enrolment in the labor market and the female participatory representation in politics. These are multidimensional inequalities that have been discovered to be interrelated and there is a common obstruction to the goals of achieving the comprehensive and sustainable development. The study also adds a sheet to the ongoing series of researches by giving the evidence which states the necessity of the specific policies aimed at decreasing the differences and rising the equal access to the opportunities and resources. The need to address these challenges is not only an ethical requirement, but its approach is also required so that sustainable and resilient communities can be developed.